Anthony Eden - Serra, Maurizio (Rivista di studi politici internazionali, 2007)
Sir Anthony Eden, later 1st Earl of Avon (1897-1977), was a leading member of the British Conservative Party between the two World Wars and after. Under-Secretary for Foreign Affairs in 1931, Lord Privy Seal (1934-1935), then Minister for the League of Nations and Foreign Secretary (1935 to 1937), Eden was in favour of reinforcing the Geneva institution. Member ofthe War Cabinet, he signed the Anglo-Soviet treaty of May 1942 and, coming back to power with Churchill in 1951, he worked to curb and to encompass the European integration process. In April 1955 he succeeded Churchill at Downing Street and, when the Suez crisis broke out, he was chiefly responsible forits awkward management, paying with his health and his political career for that. In describing the troubled personality of Anthony Eden and thoroughly analysing his choices, ambiguous and unsteady, the Author draws a critical portrait of him, as a dandy in British foreign politics.RÉSUMÉ - A. R. Eden (1897-1977) fut un des membres du parti conservateur britannique parmi les plus éminents de sa génération. Élu à la House of Commons déjà en 1923, il s’occupa presqu’exclusivement de politique étrangèrependant toute sa carrière politique. Sous-secrétaire d’État au Foreign Office en 1931, garde des sceaux de 1934 à 1935, puis ministre d’État pour la Société des Nations, ministre des Affaires Étrangères de 1935 à 1937, Eden appuya les idéaux sociétaires. Membre du Cabinet de guerre britannique, il négocia le traité anglo-soviétique de Mai 1942 et, revenu au pouvoir avec Churchill en 1951, il exerça une fonction de ralentissement sur la construction européenne.Devenu Premier ministre en avril 1955, il fut le principal responsable de la gestion maladroite de la crise de Suez, de laquelle il sortit ses nerfs épuisés et sa carrière politique irrémédiablement brisée. À la lumière des troubles de sapersonnalité et de ses choix politiques ambigus ou irrésolus, l’Auteur dessine un portrait critique de ce dandy de la politique étrangère britannique.